The moral witness : trials and testimony after genocide - Dean, Carolyn J. (Carolyn Janice), 1960- (Ithaca ; London : Cornell University Press, 2019)
"The Moral Witness maps the emergence of a 'witness to genocide' over a century, from its origins in interwar court trials to the Jewish Holocaust survivor and to today's global witness, who represents new obligations to suffering humanity at home and abroad"--
The witness as righteous avenger : the Tehlirian and Schwarzbard trials, 1921 and 1927 -- The concentration camp witness : the libel cases of Victor Kravchenko and David Rousset, 1949 and 1951 -- The Holocaust survivor witness : the Eichmann trial -- The global witness and the counter witness.
Includes bibliographical references and index.
Keywords: Genocide -- Historiography; Genocide -- Moral and ethical aspects; Witnesses; Genocide survivors; Trials (Genocide)